Correction to: Adult plant stem rust resistance in durum wheat Glossy Huguenot: mapping, marker development and validation - Mago, Rohit; Chunhong Chen; Xiaodi Xia; Whan, Alex; Forrest, Kerrie L.; Basnet, Bhoja Raj; Perera, Geetha; Chandramohan, Sutha; Randhawa, Mandeep S.; Hayden, Matthew; Bansal, Urmil; Huerta Espino, Julio; et al. (Springer, 2022)
In the original manuscript we characterize the KASP marker IWB32429, linked to the adult plant stem rust resistance locus Sr63. We describe allele specific primers which were tagged with FAM and HEX. Unfortunately, we have since found that the Tags should be reversed. We present here the correction in the methods section and also the revised Table 4 and Table S3.